Current situation and strategies of agricultural industries structure adjustment in Zhejiang Province - YAN Li-jiao; WANG Zi-qiang; GAO Qin-jian; WANG Yang-jie (浙江大学学报. 农业与生命科学版)
Over the past two decades, agricultural industries structure adjustment in Zhejiang Province has made great progress: the three main industries of rural economy developed harmoniously; the agricultural productivity has improved greatly; cropping industry was still the most important one among all industries in agriculture system; and forestry, animal husbandry, fishery and sideline production developed in an all-round way; the area of high quality rice has expanded, the proportion of autumn food area has increased, and the structure of cropping system has been optimized steadily. However, presently there still exist a number of problems in adjusting the agricultural industries structure. For example, the sustainable development of agriculture is threatened because of the increasingly serious environmental problems encountered. The area of food crops is too large, and most agricultural products are not quite suitable for export owning to lack of distinguishing quality. The farm scale is too small, and the service systems and markets are not sufficiently mature as yet. Information, technology and capital are not ready to support agricultural development yet. Accordingly, some suggestions on agricultural industries structure adjustment are put forward, such as protecting the environment, improving the quality and benefit of agricultural products, and strengthening our effort in betterment of services regarding technology, information, capital, and marketing. Practical measures should be geared to the existing problems in the three main agricultural industries. Concrete strategies for the regionalization, specialization and industrialization of agricultural industries should be undertaken, so as to further promote the modernization and sustainable development of agriculture and rural areas in Zhejiang Province.